A new species of Microhyla Tschudi, 1838 (Anura: Microhylidae) from West Coast of India: an integrative taxonomic approach - Vineeth, Kumar K.; Radhakrishna, U. K.; Godwin, R. D.; Anwesha, Saha; Rajashekhar, K. Patil; Aravind, N. A. (Zootaxa, 2018)
A new species of microhylid frog Microhyla kodial sp. nov. from the west coast of India is described in this paper. It is distinct from all described species of Microhyla occurring in South and Southeast Asia as revealed by a combination of morphological, molecular and acoustic characters. The new species is characterized by absence of lateral body stripe, tuberculated dorsal skin surface, absence of webbing between fingers, presence of basal webbing between toes and absence of dorsal marginal groove on finger and toe disc. Each male advertisement call lasts for 0.11–0.42 s and is comprised of 2–7 pulses with a dominant frequency of 3.3–4.2 kHz. The breeding season is short, limited to the rainy season (June to September) and the females lay up to 300 eggs per clutch. A molecular phylogenetic tree constructed using the mitochondrial 16S rRNA gene shows that M. kodial sp. nov. is closely related to the M. achatina group from Southeast Asia. The uncorrected genetic divergence between the new species and its closest congeners M. heymonsi, M. mantheyi, M. borneensis and M. orientalis were 7.3–7.6 %, 7.5–7.8%, 7.8–8.1% and 8.1–8.4% respectively. At present, this species is known only from the type locality, a highly disturbed urban and industrialized area which needs conservation intervention.